The development and application of multiplex real-time reverse transcriptase polymerase chain reaction assays for the detection of enteric viruses on berry fruits and in water samples - Taylor, Maureen Beatrice (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 2013.